Identification code of culture - N. Reid; N. A. Vasilchenko (Дискурс профессиональной коммуникации, 2019)
Review of Khairullin V.I. (ed.) (2018). Jazik kak identifikatsionnij kod kultury [Language as the identification code of culture]. Proceedings of the international scientific conference. Ufa. (in Russian).